Relationshiop of PPE Use, Years of Employment, and Personal Hygiene to Contact Dermatitis Symptoms - Aurellia, Almira; Haqi, Dani Nasirul (Universitas Teuku Umar, 2022)
The incidence of occupational contact dermatitis in Indonesia is high. PT Semen Indonesia (Persero) Tbk. Gresik Factory is a company which produces various types of cement as a building material. Contact dermatitis is very prone to occur among cement factory workers due to contact of cement dust with the workers' skin. This study is a quantitative study with a cross-sectional approach. The method of data collection was performed by observation and questionnaire completion. The number of respondents in this study is a total population of 30 worker units from the finish mill and packer. This study uses statistical tests with univariate and bivariate tests, namely the chi-square test. The results of this study indicate there are 20% of workers who experience symptoms of contact dermatitis, and there is a correlation between the use of PPE (p-value = 0.003), years of employment (p-value = 0.001), and personal hygiene (p-value = 0.002) with symptoms of contact dermatitis. To be able to reduce the risk of developing contact dermatitis symptoms, it is advised that workers increase awareness in the use of PPE according to standards, such as not rolling up the sleeves and using standard respirators. In addition, the workers with new category of years of employment are advised to recognize the locations of cement dust exposure and know how to prevent cement dust exposure. Workers are also advised to clean themselves directly after being exposed to cement dust after work and change into clean work clothes every day.